Focused community business model: transforming entrepreneurial mindset through relationship-building - Jakaria Dasan; Fatimah Ahmedy (ASIAN SCHOLARS NETWORK, 2020)
This paper introduces a hypothetical business model that focuses on sustaining the household incomes of the people in focused communities. A focused community can be viewed as a group of people living in close proximity led by local leaders that share common socioeconomic resources to foster sustainability in the growth and expansion of the peoples' lifestyles and interests. The business model introduced is implemented based on relationship-building between academia and the focused community. The main objective of the focused community business model is to implement projects that would generate continuous income for the community. The studied focused community is located in Marakau Village of Ranau district, Sabah. Main projects introduced were goat breeding, "fish-tagal", handicraft, poultry farming, and machete-making workshop. It can be concluded that, the basis of the focused community business model is to ensure that every member of the community involved can generate income consistently while reducing the risk of a project being interrupted along the way. The idea of the collaborative universities in the profit-sharing is merely to get rid of the subsidy mentality that has long been the stumbling block of community sustainability in improving their socioeconomic development. Hence, various business activities need to be created that are subjected to the guided questions of how to uplift the business mindset of the community, and what are the right strategies to be implemented. Herein the needs for a concrete relationship-building between the focused community, academia, stakeholders and industries is warranted.